DUSP1 Gene Polymorphisms Are Associated with Obesity-Related Metabolic Complications among Severely Obese Patients and Impact on Gene Methylation and Expression. (6th August 2013) - Guénard, F.; Bouchard, L.; Tchernof, A.; Deshaies, Y.; Hould, F. S.; Lebel, S.; Marceau, P.; Pérusse, L.; Vohl, M. C.
Abstract : The DUSP1 gene encodes a member of the dual-specificity phosphatase family previously identified as being differentially expressed in visceral adipose tissue (VAT) of severely obese men with versus without the metabolic syndrome. Objective. To test the association between DUSP1 polymorphisms, obesity-related metabolic complications, gene methylation, and expression levels in VAT. Methods. The DUSP1 locus and promoter region were sequenced in 25 individuals. SNPs were tested for association with obesity-related complications in a cohort of more than 1900 severely obese individuals. The impact of SNPs on methylation levels of 36 CpG sites and correlations between DNA methylation and gene expression levels in VAT were computed in a subset of 14 samples. Results. Heterozygotes for rs881150 had lower HDL-cholesterol levels (HDL-C; P = 0.01 ), and homozygotes for the minor allele of rs13184134 and rs7702178 had increased fasting glucose levels (P = 0.04 and 0.01, resp.). rs881150 was associated with methylation levels of CpG sites located 1250 bp upstream the transcription start site. Methylation levels of 4 CpG sites were inversely correlated with DUSP1 gene expression. Conclusion. These results suggest that DUSP1 polymorphisms modulate plasma glucose and HDL-C levels in obese patients possibly through alterations of DNA methylation and gene expression levels.